Metabolite Profiling and Bioprospecting of Acrolejeunea fertilis (Reinw., Blume & Nees) Schiffn. from Kebun Raya Cibodas, West Java - Ramadhani, Nadhifa Tazkia; Handayani, Windri; Yasman, Yasman; Putrika, Afiatry (BIOEDUSCIENCE, 2024)
Background: Acrolejeunea fertilis (liverwort) is known for having various potential natural products. However, its abundance is limited, and its secondary metabolites have not been extensively investigated. The in vitro culture technique might enhance its biomass. Methods: This study aimed to investigate the metabolite profile of A. fertilis from Kebun Raya Cibodas grown in situ and in vitro. The bioactivity, including antioxidant, total phenolic, and flavonoid content and antibacterial activity, was also evaluated. The in vitro culture of A. fertilis used ½ MS media with the addition of 0,1 mg/L of 2,4-D and one mg/L of Kinetin. Methanol and n-hexane were used for extraction. Gas Chromatography-Mass spectrometry (GC-MS) is used for metabolite profiling. Results: The optimum IC50 value from n-hexane extract is 68,18±2,65 mg/L. The highest yield of total phenolic and flavonoid content from in situ methanol extract, which resulted in 130,68±0,002 µgGAE/gr and 5,97±0,01 µgQE/gr, respectively. Antibacterial activities were evaluated by measuring the zone of inhibition for S. aureus and E. coli. The optimum area measured from in situ n-hexane extract was 23,91±1,54 and 13,08±0,23 cm, respectively. Conclusions: These findings carry important implications for the further development of natural products obtained from liverwort regarding its potential as a bioactive compound.